Role of Exosomal miRNAs in Heart Failure - Xue, Ruicong; Tan, Weiping; Wu, Yuzhong; Dong, Bin; Xie, Zengshuo; Huang, Peisen; He, Jiangui; Dong, Yugang; Liu, Chen (Frontiers in Cardiovascular Medicine, 2020)
Heart failure is the terminal outcome of the majority of cardiovascular diseases, which lacks specific diagnostic biomarkers and therapeutic targets. It contributes to most of cardiovascular hospitalizations and death despite of the current therapy. Therefore, it is important to explore potential molecules improving the diagnosis and treatment of heart failure. MicroRNAs (miRNAs) are small non-coding RNAs that have been reported to be involved in regulating processes of heart failure. After the discovery of miRNAs in exosomes, the subcellular distribution analysis of miRNAs is raising researchers' attention. Growing evidence demonstrates that exosomal miRNAs may be promising diagnostic and therapeutic molecules for heart failure. This review summarizes the role of exosomal miRNAs in heart failure in the prospect of molecular and clinical researches.